Cash Waqf Linked Social Entrepreneur - Febriyanti, Novi; Ihsani, A. Fikri Amiruddin (el-Qist : Journal of Islamic Economics and Business (JIEB), 2020)
Al-Khaibar minimarket’s one of development results of cash waqf linked social entrepreneur from productive waqf management inpatient rooms of the Very Important Person (VIP) class at Hospital of UNISMA Malang. The purpose of this study was to determine management and development of productive waqf through Al-Khaibar minimarket business at the UNISMA foundation and distribution of benefits at productive waqf management through Al-Khaibar minimarket business at the UNISMA foundation. The research method used descriptive qualitative using a sociological and empirical approach. Researcher took object of research at State Islamic University of Malang (UNISMA) related to management of cash waqf linked social entrepreneurs. The results of this study prove that productive waqf management used in accordance with George R Terry’s theory namely planning, organizing, actuating and controlling. While distribution of benefits at productive waqf management is from net profits, 20%-30% is distributed to mauquf ‘alaih, 10% for nadzir in accordance with Law of Waqf No. 41 of 2004 paragraph 12 and 60%-70% for development of waqf. Key Words: productive waqf; social entrepreneur; minimarket. Abstrak: Minimarket Al-Khaibar adalah salah satu hasil pengembangan cash waqf linked social entrepreneur dari ruang rawat inap kelas VIP di Rumah Sakit UNISMA Malang. Tujuan dari penelitian ini adalah untuk menentukan manajemen pengelolaan dan pengembangan wakaf produktif melalui bisnis minimarket Al-Khaibar di Yayasan UNISMA serta distribusi hasil manfaat wakaf produktif melalui bisnis minimarket Al-Khaibar di Yayasan UNISMA. Metode penelitian menggunakan deskriptif kualitatif dengan pendekatan sosiologis dan empiris. Peneliti mengambil objek penelitian di Universitas Islam Malang (UNISMA) terkait cash waqf linked social entrepreneur. Hasil penelitian membuktikan bahwa manajemen pengelolaan wakaf produktif yang digunakan sesuai dengan teori George R Terry yaitu planning, organizing, actuating dan controlling. Sementara distribusi hasil manfaat wakaf produktif adalah dari laba bersih, 20%-30% didistribusikan ke mauquf ‘alaih, 10% untuk nadzir yang sesuai dengan UU Wakaf No. 41 Tahun 2004 Pasal 12 dan 60%-70% untuk pengembangan wakaf.